Penambahan Berbagai Jenis Tepung Sebagai Upaya Peningkatan Pertumbuhan Dan Tingkat Kecerahan Warna Ikan Mas Koi (Cyprinus Carpio) - Alvionita, Mita; Mulis, Mulis; Amriani, Mega; Suherman, Sutianto P. (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2024)
Feed is very important in the development of fish farming because around 70% of fish farming production costs come from providing feed. To support the growth and brightness of the color of koi carp, it is necessary to have nutritional content and β-carotene according to the fish's needs. Feed that meets the nutritional needs of fish can increase the growth and color brightness of koi carp. This research aims to determine the effect of feed doses containing shrimp head meal, carrot flour and red spinach flour on the growth and color brightness of koi carp.This study aims to determine the effect of feed doses containing shrimp head meal, carrot flour and red spinach flour on the growth and brightness level of koi goldfish. This research was carried out from November to December 2022 at the Tatelu Freshwater Aquaculture Fisheries Center (BPBAT). The method used was an experimental method with a completely randomized design (CRD) consisting of 4 treatments and 3 replications. Treatment A = (control giving 5% feed dose without containing shrimp head meal, carrot flour and red spinach flour) treatments B, C, and D (feeding containing shrimp head meal, carrot flour and red spinach flour dose 5%, 10 % and 15%). In order to find out the results of the influence of feeding containing shrimp head waste flour, carrot flour and red spinach flour, the data obtained includes the results of calculating the level of color brightness and growth in koi fish calculated using analysis of variance (ANOVA)Based on the results of the study, absolute length growth in treatment D with a dose of 15% had a very significant effect with a value of 1.56 cm, while for the brightness of the color in treatment C, with a dose of 10%, it had a very significant effect with an average value of 10.69, while the growth weight and survival of koi goldfish were not significantly different.